A Translation Variation of simple Sentences in Linguistics Across Cultures Into Linguistik In Pelbagai Budaya - UTAMI, IKA NDS (2012)
This research studies about the translation variation of simple sentences in Linguistics Across Cultures into Linguistik di Pelbagai Budaya. The objectives of the study are to classify the variations of simple sentences, to determine the most strategy used and identify the accuracy of the strategy used in the variation of simple sentences. This research is a descriptive qualitative research. The object of the research is variation of simple sentence found in Linguistics Across Cultures and its translation Linguistik di Pelbagai Budaya. The data are taken from the sentences containing simple sentence. They are collected from both books by using documentation method. She applies comparison method in analyzing the data of the study. The result of data analysis shows that there are eight variations in simple sentences. From the 60 data found by the researcher, 28 data or 43,3% are active sentence which is translated into active sentence, 6 data or 10% are passive sentence that is translated into passive sentence, 2 data or 3,3% are passive which is translated into active sentence, 1 data or 1,6% active translated into passive sentence, 13 data or 21,6% are nominal sentence translated into nominal, 2 data or 3,3% are nominal sentence translated into verbal sentence, 4 data or 6,6% are verbal sentence translated into nominal sentence, and 4 data or 6,6% are simple sentence is translated into complex sentence. The strategy used in the translation of variation of simple sentences that occurs in Linguistics Across Cultures Book and its translation are divided into three, namely: addition information, there are 26 data or 40%, deletion information there are 18 data or 30%, and structural adjustment there are 16 data or 30%. The accuracy of the variation of simple sentence based on the meaning found in Linguistics Across Cultures Book are 60 data 100% is accurate translation and 0% data inaccurate translation.